Factors Influencing the Demand of Imported Milk Powder in Sri Lanka - Thangarajah, T.; Sooriyakumar, K.; Sireeranhan, A. (University of Jaffna, 2016)
This paper studies the factors that influence the import of milk powder in Sri Lanka. Only 33 percent of total milk requirement of country was supplied by the local livestock industry. Imports of dairy products alone accounted for 2.5% of Trade balance deficit in 2013. Annual data from 1996 to 2013 were used to estimate the demand function of imported milk powder. This study indicates that one percent increase in the price of imported milk powder decrease the demand for imported milk powder by 2.39%and one percent of increase in the domestic fresh milk production associated with 0.16 percent decrease in the demand for imported milk powder. When real Gross Domestic Product (GDP) increases by one percent, the demand for imported milk powder increases by 4.8 percent. This suggests that a tariff policy to restrict imports of milk powder will be effective. This study suggests that both local and multinational key players of Sri Lankan dairy market should establish milk collecting centers to increase the local milk powder and other milk food items. Fresh milk production can be significantly increased by breading programs, artificial insemination services and other veterinary services as they assist to maintain and expand the population of healthy milking cows.
Keywords: Demand Function; Imported Milk Powder